Three-dimensional finite element analysis comparative model of tooth–implant nonrigid fixation. (April 2021) - Muradyan, Tigran A; Muradyan, Nshan A; Verlinski, Sergey V; Poghosyan, Anna Yu
Connecting implants with teeth is sometimes considered for the support of prostheses in partial edentulism, especially in periodontally compromised and surgical treated patients. The aim of this study is the presentation of a model of tooth–implant nonrigid fixation in comparison with implant–implant and implant–tooth rigid fixation by three-dimensional (3D) finite element analysis. As a model, a situation with a mandibular second premolar and two molars edentulism was selected. Two implantation options with three prosthetics designs were considered. The comparative analysis of stress and strain distribution values under vertical 100 and 200 N loading was performed. The highest peri-implant crestal bone stress distribution was observed in the model with the implant–tooth rigid fixation with 200 N vertical loading with results of 136.56 MPa. In the model with implant–tooth nonrigid fixation, the maximum strain value was observed in the tooth–connector zone and the stress distribution was higher in the connectors and the prosthesis pontic zone, with a maximal value of 27.77 MPa. The design of a tooth–implant fixed denture could be suggested as a method of choice for rehabilitation of the posterior edentulous segment in cases when only one distal implant could be installed. Further clinical research is required to obtain reliable validation data for the proposed method.